Rancang Bangun Sistem Pakar Berbasis Web untuk Diagnosa Penyakit - Nurhandayani; Rasyid, Rasmiati; Sumpala, Andi Tenri; Zubaedah, Reza (Perhimpunan Ahli Teknologi Informasi dan Komunikasi Indonesia, 2025)
The progression of information technology has facilitated the creation of web-based expert systems that aid in disease diagnosis. This work is to create and implement a web-based expert system that delivers diagnostic outcomes based on user-entered symptoms. The system is designed utilizing the Rapid Application Development methodology to expedite the design and implementation process. The system's knowledge base comprises disease data, symptoms, and inference rules utilized in the diagnosis process. The test results demonstrate that all system functionalities operate as intended. Black Box testing verifies the proper functionality of each system component, encompassing disease data management, symptom input, and the diagnostic process, ensuring error-free operation. The web-based solution provides consumers with flexible access to preliminary health information. The deployment of this system is anticipated to aid the public in performing preliminary consultations prior to obtaining direct medical advice